Título Padrão - Aseff, Marlova (Revista de Letras, 2023)
This paper is a commented translation of the short story "Nadie encendía las lámparas", by the Uruguayan writer Felisberto Hernández (1902-1964). The commented translation is considered a privileged moment of union between the practice and the theory of translation, but here translation and commented translation are considered as experience and reflection. Based on Adorno, Meschonnic, Berman, Aristóteles, Heidegger and Gadamer, translation is discussed focusing on the possible relations between theory and practice, experience and reflection. Next, a brief critical study of the text is presented followed by definition of a project for this translation, which basically took into account three aspects: a) keeping the colloquial register characteristic of FH's writing; b) identifying the maintenance of a network of signifiers, such as the verbs related to the action of looking, the lexicon related to light and/or darkness; and c) seeking the naturalness of the expression in the Brazilian Portuguese language, despite the proximity of Portuguese and Spanish, trying not to make a translation too close to the syntax of the original. In parallel to the critical analysis of the text, the translation choices are commented. The complete translation is attached to this study.